(untitled) (International Journal of Scientific Trends, 2025)
This article analyzes the process of organizing football clubs in higher education institutions and their role in shaping students’ health and promoting a healthy lifestyle. The research provides an in-depth examination of the organizational model of football clubs, their implementation as extracurricular activities, and their impact on the physical, mental, and social development of young people. Additionally, the study explores factors contributing to the widespread promotion of a healthy lifestyle, prevention of harmful habits, and the development of sports culture among students through these clubs. The article also presents organizational and methodological recommendations for improving the operation of football clubs. The research findings practically demonstrate the educational and health-promoting role of football within the academic environment.